Prevalencia de alteraciones en la función pulmonar de la población residente vecina a dos fábricas de material particulado, corregimiento La Sierra, Municipio de Puerto Nare (Antioquia, Colombia), 2008 (2011)
ABSTRACT: To determine lung function and the conditions of exposure to particulate matter produced by two factories among 264 residents in the township of La Sierra, in Puerto Nare municipality of Antioquia, in 2008. Methodology: spirometries were performed and a questionnaire of respiratory symptoms was applied. Particulate matter smaller than 10 micrometters (PM10), temperature, humidity, wind direction and precipitation during six months were measured. Results: 7.2% of the people showed the lowest percentage of forced expiratory volume (FEV) below 70%. A total amount of 27.7% and 28% had FEV1 and forced vital capacity (FVC) below 80%. The largest number of people tested with the % FEV <70% lives in the four neighboring districts nearby the factories. Statistical association was found between body mass index greater than 25 and FVC < 80% (p < 0.0009), residence time and FVC < 80%. The average concentration of PM10 during the six month period was 42.1 ug/m3 and the highest was 142.89 mg/m3 . Conclusion: a significant percentage of the population has alterations in their respiratory function, mainly those living near the factories showing concentrations of PM10 which is considered a hazard. All this means a serious public health problem according to its environmental, health and social equity components all of which are not being properly operated. It requires an appropriate intervention that should become a model to implement policies to protect the population in terms of exposure to environmental pollution.